Continuous thermosalinograph oceanography along RV SONNE cruise track SO292 - Christian Betzler; Michael Schlundt (PANGAEA, 2023)
Underway temperature and salinity data was collected along the cruise track with two autonomous measurement systems, called self-cleaning monitoring boxes (SMBs). Usually, the SMBs are changed after ~12 hours. While temperature is taken at the water inlet in about 4 m depth, salinity is estimated within the SMB from conductivity and interior temperature. No temperature and salinity calibration were performed. For details to all processing steps see Data Processing Report.